The effect of disinfectants on the surface quality of irreversible hydrocolloid impression material and gypsum cast - Dulaimi, suha; Al-Wahab, zahraa (Iraqi National Journal of Nursing Specialties, 2012)
Objective: To evaluate the changes in the surface quality of irreversible hydrocolloid impression material hydrogum following disinfection with 0.525% sodium hypochlorite, 0.2% Chlorehexidine Gluconate, and 4% Povidone Iodine. Methodology: Forty specimens of alginate impression materials hydrogum were fabricated according to the ISO 1563 and were divided into four groups according to the method of solution dipping: group 1: Dip in 0.525% sodium hypochlorite, group 2: Dip in 0.2% chlorhexidine gluconate, Group 3: Dip in 4% Povidone Iodine, Group 4: No treatment with any solution (control group). Then the specimens were poured in type II stone. Surface detail was determined using a stainless steel block in accordance with ISO 1563. Results: The results were subjected to Kruskal – Wallis non parametric test showed no statistical significant difference in the effect of the disinfection solution on the surface detail quality (P – value 0.392, at p> 0.05). However, the surface quality of the specimens disinfected by sodium hypochlorite showed some degree of erosion or damage to the surface quality of the resultant cast, but the difference was not statistically significant. Recommendations: make microbiological study to evaluate the effect of disinfectant solutions on different microorganisms present in the oral cavity and evaluate the hardness of impression material following the use of disinfectant solutions.